Animal Bones, Bone Artefacts and Bone Working at Late Bronze Age Fortified Settlements in North-Eastern Lithuania: Sokiškiai, Mineikiškės and Garniai I - Luik, Heidi; Piličiauskienė, Giedrė; Podėnas, Vytenis; Micelicaitė, Viktorija; Minkevičius, Karolis; Čivilytė, Agnė (Archaeologia Lituana, 2022)
The article discusses artefacts made of osseous materials found in the Late Bronze Age fortified settlement sites in north-eastern Lithuania. Earlier, Bronze Age bone items from three Lithuanian sites – Narkūnai, Nevieriškė and Kereliai – have been analysed more thoroughly. Of sites discussed here, Sokiškiai has been archaeologically investigated in the beginning of the 1980-ies. In recent years, research has been carried out on the fortified settlements of Mineikiškės and Garniai I. 14C AMS dates have been used to date new sites as well as to specify the dates of previously studied settlements. During this research, approximately half a hundred bone, antler and tooth objects were examined, and the material used to make them was determined, if possible up to the species and skeletal part. Among the materials used, bone predominated, antler was used less, and teeth were used in only a few cases. An overview is given of the common types of bone objects, the processing techniques used to make them and the uses of the objects. The majority of tools are chisels and scrapers, and awls and points, many of which could have been used as leather working tools. The third major group of finds is bone pins, which testify to the clothing fashion that needed pins for attachment. Comparing the finds of Late Bronze Age fortified settlements in Lithuania, Latvia, Estonia, and Byelorussia, greater similarity can be observed in certain types of bone artefacts in south-eastern Latvia, north-western Byelorussia, and north-eastern Lithuania.
Keywords: Late Bronze Age; north-eastern Lithuania; fortified settlements; bone and antler artefacts; bone and antler working